(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This article presents the investigation of artivism in clowning, having as a source of analysis the caravans of the group “Mothers in Rebellion” and thus problematizing aesthetic and ethical issues of these artistic actions. Therefore, this research began its course by describing the reality and the political and ethical position of the caravans with the “Clowns in Rebel” in “Learning to be Rebel”. Then, with “Affective artivism”, reflections are developed on the philosophical concept of affection and artivism as a tool that enhances the action of joy. The research then developed the concept of declowning in “From personal failure to collective failure”, thus expanding to reflections on the renewal of the practice of clowning based on the concept of nhandereko and teko porã, expressions that in Guarani represent “good living”.